(untitled) (1820-Revista de Ciência Política, 2026)
The 21st century prioritizes the ocean as a critical concern, a natural element that covers 70% of Earth´s surface with a specific role in the Earth system, a great conveyor that gives life to human beings and feeds them. The ocean is also used for transportation with 90% of it is done by sea.